An Investigation on the Activation Energy and Thermal Degradation of Biocomposites of Jute/Bagasse/Coir/Nano TiO2/Epoxy-Reinforced Polyaramid Fibers. (23rd June 2022) - Fayaz, H.; Karthik, K.; Christiyan, K. G. Jaya; Kumar, M. Arun; Sivakumar, A.; Kaliappan, S.; Mohamed, M. Jinnah Sheik; Subbiah, Ram; Yishak, Simon
Abstract : Polyaramid is a type of aromatic polyamide that is used to strengthen materials due to its great thermal stability. The effect of adding 2 wt% of nano titanium oxide and 5% polyaramid fibers to an epoxy matrix composite reinforced with three distinct natural fibers (jute, bagasse, and coir fibers) on the structure and characteristics of the composite was examined in this study. Hand lay-up approach was used to manufacture 40 wt. percent each fiber, separately reinforced biocomposites with the addition of polyaramid, and TGA experiments were used to investigate the thermal stability of jute/bagasse/coir composites with polyaramid. The thermal degradation of the polymer took place in five steps, according to the Broido plots, with the second step being the slowest and rate determining. Because less energy is used to remove hemicellulose and loosely binding water contained in bagasse fiber, Broido plots revealed that the first step heat degradation had the lowest activation energy (Ea).